1982
DOI: 10.1080/03015521.1982.10427882
|View full text |Cite
|
Sign up to set email alerts
|

‘Grasslands Roa’ tall fescue: Herbage dry matter production and quality under mowing

Abstract: In pure swards at sites in 4 regions of New Zealand, Roa and S170 tal1 fescue (Fesluca arundinacea Schreb.) established slower than Ariki rye grass (Lolium x hybridum Hausskn). Ariki rye grass was generally superior to tall fescue at sites where soil moisture levels were maintained throughout the year (because of even rainfal1 or heavier soils), whereas tall fescue was more productive in areas prone to long periods of moisture stress (summer drought andlor light soils) particularly over the summer-autumn perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There was no difference between Roa and S170 in production or acceptability to animals, as sheep satisfactority grazed both cultivars. Differences in acceptability reported by Anderson et al (1982) may have been masked by the buffering effect of the large proportion of volunteer grasses present.…”
Section: Discussionmentioning
confidence: 71%
“…There was no difference between Roa and S170 in production or acceptability to animals, as sheep satisfactority grazed both cultivars. Differences in acceptability reported by Anderson et al (1982) may have been masked by the buffering effect of the large proportion of volunteer grasses present.…”
Section: Discussionmentioning
confidence: 71%
“…Buenos Aires). In New Zealand, tall fescue has been recommended as an option where summer drought limits the persistence of ryegrass (Lolium perenne L.) (Anderson 1982;Anderson et al 1982;Brock 1982). The greater ability of tall fescue than other grass species to tolerate drought has been related to its higher root density at depth (Garwood and Sinclair 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al (1982) found that the hypomagnesaemia ratio, K/(Ca + Mg), was wider in Roa tall fescue than in Ariki long-rotation hybrid ryegrass. Sleper et al (1977a) showed heritable variation for the ratio and for the elements separately.…”
Section: Forage Qualitymentioning
confidence: 99%